The expansion of organised crime in business activities in the North (Rivista di Studi e Ricerche sulla criminalità organizzata, 2016)
his research, conducted within the Department of Law of Bocconi University in Milan, aims to empirically ascertain the actions implemented by the Office of the Public Prosecution and the Court of Milan to counteract the Mafia’s infiltration in economic activities in the period from 2000 to 2015.All the records pertaining to criminal proceedings opened (and accessible) in the relevant period - and in relation to which preliminary investigations were closed - were consulted in their entirety. The proceedings were then followed up until the Court of Cassation.In addition, all the records and final decisions issued by the Tribunale di Prevenzione (Court for preventive measures) of Milan during the above timeframe were also considered with particular focus on preventive measures against assets.Finally this research took account of the flows of proceedings involving Article 416-bis of the Italian criminal code, as well as of the proceedings before the Court of Milan and before the Courts of Rome, Napoli, Reggio Calabria and Palermo.The information gathered from these records were finally processed by means of a specific software in order to obtain the correlations and statistics deemed to be of greatest interest, in this case with reference to the penetration in the economic and business sector.Keywords: mafia; organised crime; ‘ndrangheta; economic activities; Northern Italia.